Predictors of Suicidal Behaviors in Canadian Adolescents with No Recent History of Depression. Issue 2 (3rd April 2017) - Weeks, Murray; Colman, Ian
Abstract : We examined risk factors for suicidal behaviors (i.e., suicidal ideation and suicide attempts) in the absence of depression during adolescence. Using 6, 788 adolescents from the National Longitudinal Survey of Children and Youth (NLSCY), we identified participants with "no recent history of depression." We then tested the effects of risk factors at age 14–15 on suicidal behaviors at age 16–17. Absence of recent depression history negatively predicted both suicidal ideation and suicide attempt. However, among those with no history of depression, substance use and the presence of a chronic illness both increased the risk of suicidal behaviors. Suicidal behavior in adolescents in the absence of depression history may be explained by factors such as substance use and chronic illness.